2009
DOI: 10.1093/eurjhf/hfp024
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and NT‐proBNP, a powerful combination of biomarkers for predicting cardiovascular mortality in elderly patients with heart failure: results from a 10‐year study in primary care

Abstract: failure (HF) is common among the elderly patients. It is essential to identify those at high risk in order to optimize the use of resources. We aimed to evaluate whether a combination of two biomarkers might give better prognostic information about the risk of cardiovascular (CV) mortality in patients with symptoms associated with HF, compared with only one biomarker. Methods and resultsFour hundred and sixty-four primary health-care patients (mean age 73 years, range 65 -87) with symptoms of HF were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
6

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 38 publications
1
39
0
6
Order By: Relevance
“…Our final primary analysis included 18 articles derived from 14 independent prospective studies, 8,9,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] consisting of 22 509 participants. Among the 14 studies, 13 reported CVD outcomes (2321 events), 8,9,27,29,31-38,40 -42 4 reported CHD outcomes (741 events), 8,9,31,39 and 4 reported stroke outcomes (828 events).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our final primary analysis included 18 articles derived from 14 independent prospective studies, 8,9,[27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] consisting of 22 509 participants. Among the 14 studies, 13 reported CVD outcomes (2321 events), 8,9,27,29,31-38,40 -42 4 reported CHD outcomes (741 events), 8,9,31,39 and 4 reported stroke outcomes (828 events).…”
Section: Resultsmentioning
confidence: 99%
“…8,9,31,37 The study characteristics are presented in Table 1. Three studies recruited subjects from a elderly population (8816 participants), 8,31,38 1 recruited persons from a general population (5067 participants), 35 5 recruited persons with CHD or stroke at entry (6701 participants), 9,33,34,37,39,42 3 recruited persons with heart failure at entry (932 participants), 27,36,40 and 1 recruited persons with asymptomatic carotid atherosclerosis (1004 participants). 41 Follow-up duration ranged from 1 42 to 12.8 years.…”
Section: Resultsmentioning
confidence: 99%
“…Cystatin C has been recognized as a sensitive marker for potential renal dysfunction and injury and an independent predictor of cardiac outcomes in patients with HF. [122][123][124][125] Recent studies have suggested that serum cystatin C can reflect artery stiffness. 126,127 Interestingly, data from a population-based study showed that high serum cystatin C levels were associated with increased left ventricular mass, concentric ventricular hypertrophy, and function.…”
Section: Circulating Cathepsins and Cystatin C As Biomarkers For Ccvdmentioning
confidence: 99%
“…[41][42][43][44] Of importance, CysC offered complementary prognostic information to other cardiac biomarkers like troponin T (cTnT), high-sensitivity CRP, and N-terminal proBNP, helping clinicians perform more accurate risk stratification of patients with acute HF or ACS. [45][46][47] KIM-1 KIM-1 is a transmembrane glycoprotein belonging to the immunoglobulin gene superfamily; it is involved in the differentiation of T helper cells and expressed on the proximal tubule apical membrane ciliae with injury but not in the normal kidney.…”
Section: Cysc In Acs and Congestive Hfmentioning
confidence: 99%